Limpet teeth microstructure unites auxeticity with extreme strength and high stiffness - Oh, Sang Ho (2023)
Materials displaying negative Poisson's ratio, referred to as auxeticity, have been found in nature and created in engineering through various structural mechanisms. However, uniting auxeticity with high strength and high stiffness has been challenging. Here, combining in situ nanomechanical testing with microstructure-based modeling, we show that the leading part of limpet teeth successfully achieves this combination of properties through a unique microstructure consisting of an amorphous hydrated silica matrix embedded with bundles of single-crystal iron oxide hydroxide nanorods arranged in a pseudo-cholesteric pattern. During deformation, this microstructure allows local coordinated displacement and rotation of the nanorods, enabling auxetic behavior while maintaining one of the highest strengths among natural materials. These findings lay a foundation for designing biomimetic auxetic materials with extreme strength and high stiffness.